iPad and its potential in education - Hloušek, Martin; Jaklová, Martina L.; Smekal, Martin; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2011)
This master thesis focuses on the Apple's iPad in the educational institutions and provides reader with the compact overview about the device in this field. Firstly, it shows the strategy of the company in the Europe and the Czech Republic. Secondly, there are mentioned iPad competitors from the different perspectives and the comparison. Thirdly, iPad usage in the schools; if it is even suitable device for this field and how students and educators can benefit from it. This is followed by the survey among the high school and university students. The questionnaire was divided into the two groups -- non-iPad users and iPad users. And lastly the thesis shows various case studies from the different schools and how the iPad can be implemented into the curriculums. Also contains recommendations and the best practises from the different high schools and universities, which can be inspiring for the new iPad pilot projects.
Vedoucí práce: Martina L. Jaklová
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2011
Rok obhajoby 2011
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses